ANALYSIS OF THE IMPLEMENTATION PATTERN OF CONTINUOUS PROFESSIONAL DEVELOPMENT FOR VOCATIONAL HIGH SCHOOL SUPERVISORS IN NORTH SUMATERA - Rahman, Arif; Sutopo, Adi; Rosneli, Rosneli; Mudjisusatyo, Yuniarto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation pattern of Continuous Professional Development (CPD) for Vocational High School (VHS) supervisors in North Sumatra, focusing on two main issues: (1) What is the current implementation pattern of CPD for VHS supervisors? and (2) What are the strengths and weaknesses in implementing the CPD? This research uses a qualitative descriptive method, with data collection techniques through in-depth interviews, observation, and document analysis. The results show that the CPD implementation pattern for VHS supervisors in North Sumatra varies in its application, with some supervisors actively participating in development activities, but there are still limitations in terms of access and consistency of training. The main strength of the CPD program lies in the support of local government policies and the initiative of supervisors to develop their competencies independently. On the other hand, weaknesses include a lack of coordination between related agencies, limited budget, and ineffective monitoring and evaluation of CPD program results. This study suggests the need for improved coordination systems, increased budgets, and continuous monitoring to enhance the effectiveness of CPD for VHS supervisors.